The Synergistic Effect of Warm Salt Footbath and Foot-Ankle Exercises in Individuals with Type 2 Diabetes Mellitus: A Study Protocol for Multicenter Randomized Controlled Trial - Sirait, Healthy Seventina; Said, Faridah Mohd; Mohamad, Nur Afiqah (Fakultas Ilmu-ilmu Kesehatan, 2024)
Individuals with type 2 diabetes mellitus (T2DM) experience issues with their sleep quality and elevated level of the neutrophil-lymphocyte ratio (NLR). Warm salt footbaths and foot-ankle exercises play a significant role in addressing inflammation and improving sleep quality. Nevertheless, no studies have examined the synergistic effects of warm salt footbaths and foot-ankle exercises. This study aims to investigate the synergistic effects of warm footbath water and foot-ankle exercises on sleep quality and NLR. A randomized controlled trial with a total of 108 individuals with T2DM randomly assigned to one four groups: a warm salt footbath, a foot-ankle exercises, a combination of both interventions, or a control group. The interventions administered over a period of 4 weeks (three times per week). Evaluations were performed by blinded evaluators at baseline, as well as after 2 and 4 weeks of interventions. Chi-squared test, one-way analysis of variance, and generalized estimating equations were employed for data analysis. The results of this trial were expected to elucidate the synergistic effects of warm salt water footbath and foot-ankle exercises on sleep quality and NLR. Furthermore, the combination of warm salt water footbaths and foot-ankle exercises is more effective either intervention alone or conventional treatment.